2022
DOI: 10.3390/v14112412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Achieving SVR on Clinical Characteristics and Surgical Outcomes in Patients Who Developed Early-Stage HCV-Related Hepatocellular Carcinoma and Received Curative Resection: Preoperative versus Postoperative SVR

Abstract: The high accessibility to healthcare and increasing awareness of hepatocellular carcinoma (HCC) surveillance after sustained virologic response (SVR) to HCV treatment allow early detection of operable HCC in Taiwan. However, the effects of achieving SVR on patient characteristics and surgical outcomes after curative resection remain elusive. We aimed to compare the clinical presentation and postoperative prognosis among patients with early-stage HCV-related HCC and different viral status. We retrospectively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Whether SVR is achieved preoperatively or postoperatively, it is associated with better prognoses of HCV-related HCC ( 135 , 136 ). Further research suggested that preoperative SVR is more beneficial than postoperative SVR, with similar surgical outcomes but better postoperative liver function ( 137 139 ).…”
Section: Extended Contentmentioning
confidence: 99%
“…Whether SVR is achieved preoperatively or postoperatively, it is associated with better prognoses of HCV-related HCC ( 135 , 136 ). Further research suggested that preoperative SVR is more beneficial than postoperative SVR, with similar surgical outcomes but better postoperative liver function ( 137 139 ).…”
Section: Extended Contentmentioning
confidence: 99%
“…[45] Individuals who achieved HCV SVR before or after HCC resection showed similar recurrence and progression-free survival, with non-SVR HCV patients presenting with a higher rate of recurrence and lower progression-free survival. [46] Bariatric surgery as a means to treat obesity driven metabolic syndrome also reduces HCC risk [47] and leads to regression of fibrosis in 70% of patients 5 years after surgery. [48] In 1992, it was reported that both prior and ongoing alcohol consumption increased risk for cirrhosis.…”
Section: Origins Of Hepatocellular Carcinomamentioning
confidence: 99%
“…In fact, the risk of progression to HCC goes beyond measures of patient liver fibrosis, and combining viral status with fibrosis, age, fibroscan assessments, and a battery of serologic tests like FIB-4, further enhances risk stratification 45. Individuals who achieved HCV SVR before or after HCC resection showed similar recurrence and progression-free survival, with non-SVR HCV patients presenting with a higher rate of recurrence and lower progression-free survival 46. Bariatric surgery as a means to treat obesity driven metabolic syndrome also reduces HCC risk47 and leads to regression of fibrosis in 70% of patients 5 years after surgery 48.…”
Section: Presentation Of “Scarring”mentioning
confidence: 99%
“…However, it is still unclear whether the SVR in such patients impacts the risk of developing HCC. Multiple retrospective studies conducted in heterogeneous subjects have reported the increased risk of HCC in such cases, while others contradict these conclusions (Hsu et al, 2022;Yeh et al, 2021). This study was conducted to assess the incidence of hepatocellular carcinoma in chronic hepatitis C patients genotype III with hepatic fibrosis or cirrhosis after achievement of sustained viral response after treatment with direct acting antivirals.…”
Section: Introductionmentioning
confidence: 99%